Neuromarketing and the decision-kaking process of the generation Y wine consumers in the Slovak Republic - Jana Němcová (Potravinarstvo, 2019)
In recent years, interest in scholarly research on buying behaviour of Generation Y has grown. However, studies are mainly realized abroad and many of them deal with this issue in general. The purpose of this paper is to identify the factors influencing the decision-making process of the Generation Y customers in the selection of wine in the Slovak Republic. A total of 21 respondents participated in the survey. Eye-tracking and a questionnaire were selected for research. For processing and evaluating the eye-tracking research, the Gazepoint Analysis UX Edition software and Microsoft Excel were used. For statistical data analysis, the Kruskal-Wallis test and Spearman's non-parametric test were performed. Based on the results of the questionnaire and the testing, a label was the most important factor. Differences were noted at the moment of examining the information on a label. The most important factor determined by the questionnaire survey was variety, or vintage year, but by using measurement, the most important factor was label design. With regard to bottle shape, the most preferred was the Bordeaux type of bottle. Testing was carried out in laboratory conditions that only simulated the real selection of wine. This could have caused the difference between conscious decision-making and unconscious visual attention. Therefore, in the future, it is recommended to carry out similar research using a mobile eye camera to realize the test with real wine bottles. It is also assumed to involve other methods to obtain information about real attention of the tested probands. The presented research provides information for winegrowers and merchants who can improve their products and communicate effectively with customers. Findings are particularly beneficial because this research is among the first carried out in this area and it was not based only on conscious participation of respondents, but also on unconscious perception, because a deeper understanding of unconscious influences, that shape consumer's decision, helps to better understand consumer's behaviour.